"3‐Day Surprise Question" to predict prognosis of advanced cancer patients with impending death: Multicenter prospective observational study. (21st December 2020) - Ikari, Tomoo; Hiratsuka, Yusuke; Yamaguchi, Takuhiro; Maeda, Isseki; Mori, Masanori; Uneno, Yu; Taniyama, Tomohiko; Matsuda, Yosuke; Oya, Kiyofumi; Tagami, Keita; Inoue, Akira
Abstract: Background: The study aimed to clarify the efficacy of the "3‐Day Surprise Question (3DSQ)" in predicting the prognosis for advanced cancer patients with impending death. Patients and Methods: This study was a part of multicenter prospective observational study which investigated the dying process in advanced cancer patients in Japan. For patients with a Palliative Performance Scale ≤20, the 3DSQ "Would I be surprised if this patient died in the next 3 days?" was answered by their physicians. In addition to the sensitivity and specificity of the 3DSQ, the characteristics of patients who survived longer than expected were examined via multivariate analysis. Results: Among the 1896 patients enrolled, 1411 were evaluated. Among 1179 (83.6%) patients who were classified into the "Not surprised" group, 636 patients died within 3 days. Among 232 (16.4%) patients of "Yes surprised" group, 194 patients lived longer than 3 days. The sensitivity, specificity, positive predictive value, and negative predictive value of the 3DSQ were 94.3% (95% confidence interval [CI]: 92.7% to 95.8%), 26.3% (95% CI: 24.8% to 27.6%), 53.9% (95% CI: 53.0% to 54.7%), and 83.6% (95% CI: 78.7% to 87.7%), respectively. Multivariate analysis showed palpable radial artery, absent respiration with mandibular movement, SpO2 ≥ 90%, opioid administration, and no continuous deep sedation as characteristics of patients who lived longer than expected. Conclusions: The 3‐Day Surprise Question can be a useful screening tool to identify advanced cancer patients with impending death. Abstract : Survival prediction in cancer patients with impending death is important for patients, families, and physicians. The 3‐Day Surprise Question can be a useful screening tool to identify advanced cancer patients with impending death.